Developing Problem-Solving Based E-Student Liveworksheet to Improve Students’ Critical Thinking in Acid-Base - Mutiara, Fadilah; Azizah, Utiya; Ramadhania, Nurina Rizka (Lectura : Jurnal Pendidikan, 2025)
This study is conducted in response to the low levels of students’ critical thinking skills, particularly in interpretation, analysis, inference, and explanation, in the context of acid-base chemistry, as well as the scarcity of digital resources that promote active learning. The objective is to develop a problem-solving-based E-Student Liveworksheet to improve critical thinking skills related to acid-base material. Research and Development (R&D) was employed, following the 4D model (Define, Design, Develop, and Disseminate). The feasibility of the developed worksheet was evaluated using Nieveen’s criteria: validity, practicality, and effectiveness. Data were gathered through expert validation forms, student questionnaires, classroom observations, and critical thinking tests. The study involved eleventh-grade students at Gedangan Senior High School. Validation results showed a mode score of 4, indicating high content validity. The practicality score from student responses reached 95%, categorized as "very good." Effectiveness was demonstrated by n-gain scores ranging from 0.50 to 1.00, reflecting moderate to high improvement across all critical thinking indicators. These findings confirm that the liveworksheet is a valid, practical, and effective tool for enhancing students’ critical thinking in acid-base learning. In conclusion, the developed digital resource supports the goals of the Independent Curriculum by fostering interactive, contextual, and problem-based learning. This innovation offers valuable potential for broader application in science education and serves as a reference for integrating technology to promote higher-order thinking. Future research is recommended to explore its long-term impact and adaptability across various scientific topics and learning environments.